Liberia Domestic Revenue Mobilization Policy Notes - World Bank (World Bank, Washington, DC, 2019)
Following general elections in Liberia in 2017, a new government was formed with a mandate to achieve ambitious development objectives. Following a nationwide consultative process, the new medium-term national development plan, Pro-Poor Agenda for Prosperity and Development (PAPD)-2019-2023 was developed focusing on: strengthening public institutions; accelerating infrastructure investments for productive capacity; improving productivity in the real sector through enhanced economic diversification; increasing investment in human capital (youth employment, health, and education); and improving competitiveness, while safeguarding macroeconomic and debt sustainability. The focus of fiscal policy should be twofold, raising revenues while sustaining deficit at financeable level. In such a tight fiscal situation, the imperative is to secure equal or improved quality of public services by prioritizing and improving the composition of expenditure, enhancing efficiency, and expanding the resource envelope by stepping up the revenue mobilization efforts. Sustaining pro-poor development agenda, will likely require a political resolve to reduce the share of government resources devoted to high paid public servants and discretionary expenditures, as well as improve the efficiency and transparency of government spending. Otherwise, the financing gap created by an announced decline in grants and other forms of external assistance may be difficult to close.